2016
DOI: 10.3389/fncom.2016.00141
|View full text |Cite
|
Sign up to set email alerts
|

Neurons in Primate Visual Cortex Alternate between Responses to Multiple Stimuli in Their Receptive Field

Abstract: A fundamental question concerning representation of the visual world in our brain is how a cortical cell responds when presented with more than a single stimulus. We find supportive evidence that most cells presented with a pair of stimuli respond predominantly to one stimulus at a time, rather than a weighted average response. Traditionally, the firing rate is assumed to be a weighted average of the firing rates to the individual stimuli (response-averaging model) (Bundesen et al., 2005). Here, we also evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 55 publications
1
36
0
Order By: Relevance
“…It is well known that such firing patterns are variable in the face of identical, highly controlled experimental conditions (such as the presentation of the same stimulus in the same context). While many studies have viewed this variability as deleterious "noise" that if unsolved would undermine the ability of the brain to perform its essential tasks [12][13][14][15][16] , we and others have sought explanations under the possibility that certain forms of such variation may contribute in a positive fashion to brain function 1,[17][18][19][20][21][22][23][24] . In particular, we have successfully modeled variation in whole-trial spike counts to multiple stimuli as being drawn from the observed distributions of spike counts to those same stimuli when presented individually 1 .…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that such firing patterns are variable in the face of identical, highly controlled experimental conditions (such as the presentation of the same stimulus in the same context). While many studies have viewed this variability as deleterious "noise" that if unsolved would undermine the ability of the brain to perform its essential tasks [12][13][14][15][16] , we and others have sought explanations under the possibility that certain forms of such variation may contribute in a positive fashion to brain function 1,[17][18][19][20][21][22][23][24] . In particular, we have successfully modeled variation in whole-trial spike counts to multiple stimuli as being drawn from the observed distributions of spike counts to those same stimuli when presented individually 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we propose measures to quantify the processing 69 mechanism in a continuum between serial and parallel processing. The method relies on 70 the probability-mixing model for single neuron processing [16], derived from the Neural 71 Theory of Visual Attention [1,17], which states that when presented with a plurality of 72 stimuli a neuron only responds to one stimulus at any given time. By probabilistic 73 modeling and statistical inference using multiple simultaneously recorded spike trains, 74 we infer and decode what the recorded neurons are responding to, providing a way to 75 distinguish between parallel processing and serial processing on a neuronal level.…”
mentioning
confidence: 99%
“…Consider an experiment in which we record the action potentials or spikes from each 79 of a number of neurons of the same type, e.g., a set of functionally similar neurons in 80 visual cortex with overlapping receptive fields (see, e.g., [16]), or neurons in prefrontal 81 cortex that are believed to be dynamically allocated to process task-relevant 82 information (see, e.g., [4]), which are the neurons we analyze in this paper. Suppose two 83 stimuli (Stimulus 1 and 2) are both within the classical receptive fields of all of the 84 recorded neurons, but otherwise the receptive fields are empty.…”
mentioning
confidence: 99%
See 2 more Smart Citations